Abundance of zirconium in the atmospheres of red giants in Galactic globular cluster 47 Tuc. Issue Volume 14:Issue S351(2019) (May 2019) - Kolomiecas, Edgaras; Dobrovolskas, Vidas; Kučinskas, Arūnas
Abstract: We determined zirconium abundance in the atmospheres of 327 red giant branch (RGB) stars in the globular cluster 47 Tuc. The 1D LTE abundances were obtained from the archival VLT GIRAFFE spectra, using 1D hydrostaticATLAS9 stellar model atmospheres and synthetic Zr I line profiles computed with theSYNTHE package. The average zirconium abundance determined in the sample of RGB stars, 〈[Zr/Fe]〉 = +0.38 ± 0.12, agrees well with zirconium abundances obtained at this metallicity in the Galactic field stars, as well as with those observed in other Galactic globular clusters.